MENCERMATI KONSEP BUSSINESS INTELIGENT DI PERUSAHAAN - Felix Gunawan (Fakultas Seni Rupa dan Desain ITB, 2006)
This article describes the advantages of applying the business intelligent concept into a company's divisions such as Human Resource Management (HMR), Research and Development (R&D), Just In Time Distribution, and Customer Relationship management (CMR). Teknologi yang